Kinematic Magnetic Resonance Imaging for Evaluation of Disc‐Associated Cervical Spondylomyelopathy in Doberman Pinschers. (30th May 2016) - Provencher, M.; Habing, A.; Moore, S.A.; Cook, L.; Phillips, G.; da Costa, R.C.
Abstract : Background: The dynamic component of disc‐associated cervical spondylomyelopathy (DA‐CSM) currently is evaluated using traction magnetic resonance imaging (MRI), which does not assess changes in flexion and extension of the cervical vertebral column. In humans with cervical spondylotic myelopathy, kinematic MRI is used to identify dynamic compressions. Hypothesis/Objectives: To evaluate the feasibility and utility of kMRI in Doberman Pinschers with DA‐CSM using a novel positioning device. We hypothesized that kMRI would identify compressive lesions not observed with neutral positioning and change the dimensions of the spinal cord and cervical vertebral canal. Animals: Nine client‐owned Doberman Pinschers with DA‐CSM. Methods: Prospective study. After standard MR imaging of the cervical spine confirmed DA‐CSM, dogs were placed on a positioning device to allow imaging in flexion and extension. Morphologic and morphometric assessments were compared between neutral, flexion, and extension images. Results: Flexion was associated with improvement or resolution of spinal cord compression in 4/9 patients, whereas extension caused worsening of compressions in 6/9 patients. Extension identified 6 new compressive lesions and was significantly associated with dorsal and ventral compression at C5‐C6 ( P = .021) and C6‐C7 ( P = .031). A significant decrease in spinal cord height occurred at C6‐C7 from neutral to extension ( P = .003) and in vertebral canal height at C5‐C6 and C6‐C7 from neutral to extension ( P = .011 and .017, respectively). Conclusions and clinical importance: Our results suggest that kMRI is feasible and provides additional information beyond what is observed with neutral imaging, primarily when using extension views, in dogs with DA‐CSM.